A model of the artificial metastasis of human epidermoid carcinoma A431 in nude mice for examination of the oncolytic activity of vaccinia virus - G. V. Kochneva; A. A. Grazhdantseva; G. F. Sivolobova; A. V. Tkacheva; A. N. Shvalov; A. Yu. Unusova; E. I. Ryabchikova; S. V. Netesov (Вавиловский журнал генетики и селекции)
Human carcinoma A431 cells were subcutaneously injected into nude mice at points remote from each other. One of the two xenografts developed afterwards was used for treatment with a recombinant vaccinia virus, while another served as an artificial metastasis. We used the attenuated recombinant vaccinia virus (VACV) VVdGF-GFP2 of the L-IVP strain (GenBank accession number KP233807), with deletion of two virulence genes: the virus growth factor and thymidine kinase, with the gene for the green fluorescent protein (GFP2) inserted in an area of the latter. Treatments were performed by a single intratumoral injection of the recombinant VACV at a dose of 107 PFU/mouse. VACV was detected in cells of the artificial metastasis as early as two days following infection, and after 8 days virus concentrations were com- parable with those in the infected tumor (~109 PFU/ml). Electron microscopy revealed selective replication of the recombinant in tumor cells. Targeted accumulation of GFP2 in both tumor and metastasis was shown in the UV-images of the mice obtained using the In-vivo Multispectral Imaging System (Bruker, Germany). Complete destruction of the tumor was registered after 12 days, and that of metastasis, after 20 days post injection of VVdGF-GFP2. The destruction process was accompanied by pronounced edema and leukocyte infiltration of tumor tissue. The recombinant virus induced a significant reduction in the sizes of the tumor and metastasis: by the end of the experiment (35 days) the xenografts in the control mice were 10 times larger than those in the treated mice (5000 vs. 500 mm3). Our study showed that the attenuated VACV administered by the peripheral route not only is able to destroy the primary tumor, but also has a distinct antimetastatic action.